Neonatal Presentation of Rhizomelic Chondrodysplasia Punctata: Spot Diagnosis and Myriads of Unmet Needs - Amarendra Prasad; Chanchal Kumar; Dhiraj Sidagonda Shedabale; Mohammad Shahbaz Alam; Suvas Chand; Ayesha Romana (Dubai Medical Journal, 2025)
Background: Rhizomelic chondrodysplasia punctata (RCDP) is an uncommon inborn error of metabolism related to peroxisome. The inheritance pattern of this problem is autosomal recessive in nature. Five genetic subtypes have been reported which are clinically indistinguishable. Majority of cases have arthrogryposis, cataract, and significant growth and neurodevelopmental impairments. Diagnosis is made by observing skeletal changes, cataract, and biochemical changes of peroxisomal dysfunction, including raised phytanic acid and reduced red cell plasmalogen level, and is confirmed by genetic analysis. The mainstay of treatment is supportive measures.